The Influence of Stakeholder Management, Teacher Characteristics, Reward Systems, On the Effectiveness of SMPIT In the Riau Islands - Saripuddin, Saripuddin; Latif, Mukhtar; Anwar, Kasful (International Journal of Education and Digital Learning (IJEDL), 2023)
This research aims to examine 4 (four) variables using path analysis. The aim of this research is to reveal the influence of stakeholder management and teacher characteristics on the effectiveness of the Integrated Islamic Junior High School which is mediated by the reward system. In this research, the author used quantitative research methods with a sample size of 90 respondents from Bahtera Insani Bintan Integrated Islamic Junior High School, Ulul Albab Batam Integrated Islamic Junior High School, Fajar Divine 1 Integrated Islamic Junior High School, Batam, Integrated Islamic Junior High School Fajar Divine 2 Batam, Insan Cendikia Karimun Integrated Islamic Junior High School and Darul Mukmin Karimun Integrated Islamic Junior High School in the Riau Islands province. The data collection method used is in the form of a questionnaire which is then processed with statistical analysis. The results include; 1). Stakeholder management has a direct effect on the effectiveness of SMP-IT by 10.1%. 2). Teacher characteristics have a direct effect on the effectiveness of SMP-IT by 10.9%. 3). Stakeholder management and teacher characteristics simultaneously have a direct effect on the effectiveness of SMP-IT by 68.7%. 4). Stakeholder management has a direct effect on the reward system by 24.6%. 5). Teacher characteristics have a direct effect on the reward system by 30.2%. 6). Stakeholder management and teacher characteristics simultaneously have a direct effect on the reward system by 79.5%. 7). The reward system has a direct effect on the effectiveness of SMP-IT by 52.7%. 8). Stakeholder management has a direct influence on the effectiveness of SMP-IT through the reward system by 40.3%. 9). Teacher characteristics have a direct influence on the effectiveness of SMP-IT through the reward system by 58.9%. 10). Stakeholder management, teacher characteristics and the reward system simultaneously have a direct influence on the effectiveness of SMP-IT by 86.6%. The conclusion is that stakeholder management, teacher characteristics and reward systems can influence the effectiveness of SMP-IT. And it can be explained that apart from being an exogenous variable, the reward system is also able to play its role as an intervening variable.